3D TUDE MOVIE SERIES “HANDBAN KEBERUNTUNGAN” - I Kadek Agus Sutrisna; Padma Nyoman Crisnapati; I Made Gede Sunarya; Made Windu Antara Kesiman (Universitas Pendidikan Ganesha, 2013)
3D animation movie titled